Exploring the Values of Character Education in the Riau Malay Folk Song "Bukoba Panglima Awang" and its Implementation in Middle School Literature Learning in the Merdeka Belajar Curriculum - Arianti, Rita; Fitrah, Yundi; Nazurty, Nazurty; Kusmana, Ade (AL-ISHLAH: Jurnal Pendidikan, 2024)
Globalization has contributed to a decline in students' moral character, with traditional values like respect for parents, teachers, and the elderly fading. To address this, schools must prioritize character education. One effective method is incorporating local cultural elements, such as folk songs, into the curriculum. This study examines the character education values in the Riau Malay folk song "Bukoba Panglima Awang" and its implementation in literature lessons for junior high school students under the Merdeka Curriculum. Using a qualitative, descriptive approach, the research identified 19 character values in the song, including politeness, humility, obedience, religious devotion, hard work, and integrity. A key value is obedience, where children are reminded to obey their parents or face divine consequences. These values are integrated into literature learning modules for 7th-grade students, with particular emphasis on politeness, humility, obedience, and compassion. The findings suggest that traditional folk songs like "Bukoba Panglima Awang" offer a rich source of character education and can be effectively used to strengthen students' moral development within modern curricula. Further research should explore how local cultural elements can be more broadly applied to foster character education in schools across Indonesia.